2014
DOI: 10.1111/1750-3841.12558
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Differences Between Beet and Cane Sugar Sources

Abstract: Research concerning the sensory properties of beet and cane sugars is lacking in the scientific literature. Therefore, the objectives of this research were to determine whether a sensory difference was perceivable between beet and cane sugar sources in regard to their (1) aroma-only, (2) aroma and taste without nose clips, and (3) taste-only with nose clips, and to characterize the difference between the sugar sources using descriptive analysis. One hundred panelists evaluated sugar samples using a tetrad test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The flavor of sucrose is generally described as purely sweet, but some distinctive flavor volatiles often persist in beet and cane sugars (Monte and Maga ; Pihlsgard ; Godshall ; Grimm and others ). Sensory differences between sugars from beet and cane sources have been found and described (Maga ; Monte and Maga ; Urbanus and others ). Urbanus and others demonstrated that panelists are able to differentiate between beet and cane sugars when evaluating the samples by aroma only and by aroma and taste together ( P < 0.05), but not when evaluating by taste alone ( P = 0.19).…”
Section: Technical and Functional Roles Of Sugars In Foods And Beveragesmentioning
confidence: 95%
See 4 more Smart Citations
“…The flavor of sucrose is generally described as purely sweet, but some distinctive flavor volatiles often persist in beet and cane sugars (Monte and Maga ; Pihlsgard ; Godshall ; Grimm and others ). Sensory differences between sugars from beet and cane sources have been found and described (Maga ; Monte and Maga ; Urbanus and others ). Urbanus and others demonstrated that panelists are able to differentiate between beet and cane sugars when evaluating the samples by aroma only and by aroma and taste together ( P < 0.05), but not when evaluating by taste alone ( P = 0.19).…”
Section: Technical and Functional Roles Of Sugars In Foods And Beveragesmentioning
confidence: 95%
“…Sensory differences between sugars from beet and cane sources have been found and described (Maga ; Monte and Maga ; Urbanus and others ). Urbanus and others demonstrated that panelists are able to differentiate between beet and cane sugars when evaluating the samples by aroma only and by aroma and taste together ( P < 0.05), but not when evaluating by taste alone ( P = 0.19). In a subsequent study, the sensory differences between beet and cane sugars from multiple sources were defined through a descriptive analysis panel (Urbanus and others ).…”
Section: Technical and Functional Roles Of Sugars In Foods And Beveragesmentioning
confidence: 95%
See 3 more Smart Citations